2015
DOI: 10.1002/mrm.25838
|View full text |Cite
|
Sign up to set email alerts
|

Utility of real-time field control in T2 *-Weighted head MRI at 7T

Abstract: Real-time field control was found to be a robust means of countering respiratory field perturbations in variable conditions encountered in high-field brain imaging. Reducing net fluctuation, it generally expands the feasibility of high-field T2 * imaging toward challenging patients and brain regions. Magn Reson Med 76:430-439, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 35 publications
10
48
0
Order By: Relevance
“…The navigator echo‐based approach used in this study can increase the total scan time, perturb signal steady‐states, or not capture field dynamics . There are various ways of removing respiratory motion effects . A correction method utilizing retrospective gating is widely used for both respiratory and cardiac motion correction in fMRI studies using an EPI sequence .…”
Section: Discussionmentioning
confidence: 99%
“…The navigator echo‐based approach used in this study can increase the total scan time, perturb signal steady‐states, or not capture field dynamics . There are various ways of removing respiratory motion effects . A correction method utilizing retrospective gating is widely used for both respiratory and cardiac motion correction in fMRI studies using an EPI sequence .…”
Section: Discussionmentioning
confidence: 99%
“…One potential use of a FC system could be research/clinical studies with elderly people, as these patients commonly suffer from dyspnea (i.e., breathing disorders due to breathlessness, chest tightness, or increased effort of breathing) . In a previous study, FC also eliminated the field fluctuations in normalT2*‐weighted images of healthy subjects with higher BMI, as a result of movement of more tissue during the breathing cycle . However, in our current study, we included young healthy volunteers without breathing problems, and the differences between reference and “no FP, with FC” QSM images were too small for a direct visual detection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The field‐probe concept has recently been extended to a feedback implementation for real‐time field compensation up to third order in space . In previous studies, it has been shown to reduce breathing artifacts in normalT2*‐weighted brain images and normalT2* maps acquired at 7 T . The purpose of this study was to assess the potential of real‐time field control to enhance gradient echo–based QSM images acquired at 7 T based on phantom and volunteer experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Navigator echoes have been used to directly track the fluctuating signal phase by measuring non‐phase‐encoded echoes interleaved with the actual data acquisition 5,7,8 which increases scan time. Examples for the use of external sensors are the signals generated by respiratory bellows 9 or NMR field probes, which have been used for real‐time compensation of the fluctuating B0 field 10,11 . The former approach increases the complexity of the examination workflow and is limited by the imperfect correlation of the breathing signal and the actual changes in B0.…”
Section: Introductionmentioning
confidence: 99%